A Translational Porcine Model for Human Cell–Based Therapies in the Treatment of Posttraumatic Osteoarthritis After Anterior Cruciate Ligament Injury. Issue 12 (October 2020) - Kremen, Thomas J.; Stefanovic, Tina; Tawackoli, Wafa; Salehi, Khosrowdad; Avalos, Pablo; Reichel, Derek; Perez, J. Manuel; Glaeser, Juliane D.; Sheyn, Dmitriy
Background: There is a high incidence of posttraumatic osteoarthritis (PTOA) after anterior cruciate ligament (ACL) injury, and these injuries represent an enormous health care economic burden. In an effort to address this unmet clinical need, there has been increasing interest in cell-based therapies. Purpose: To establish a translational large animal model of PTOA and demonstrate the feasibility of intra-articular human cell–based interventions. Study Design: Descriptive laboratory study. Methods: Nine Yucatan mini-pigs underwent unilateral ACL transection and were monitored for up to 12 weeks after injury. Interleukin 1 beta (IL-1β) levels and collagen breakdown were evaluated longitudinally using enzyme-linked immunosorbent assays of synovial fluid, serum, and urine. Animals were euthanized at 4 weeks (n = 3) or 12 weeks (n = 3) after injury, and injured and uninjured limbs underwent magnetic resonance imaging (MRI) and histologic analysis. At 2 days after ACL injury, an additional 3 animals received an intra-articular injection of 10 7 human bone marrow–derived mesenchymal stem cells (hBM-MSCs) combined with a fibrin carrier. These cells were labeled with the luciferase reporter gene (hBM-MSCs-Luc) as well as fluorescent markers and intracellular iron nanoparticles. These animals were euthanized on day 0 (n = 1) or day 14 (n = 2) after injection. hBM-MSC-Luc viability and localization were assessed using ex vivo bioluminescence imaging, fluorescence imaging, and MRI. Results: PTOA was detected as early as 4 weeks after injury. At 12 weeks after injury, osteoarthritis could be detected grossly as well as on histologic analysis. Synovial fluid analysis showed elevation of IL-1β shortly after ACL injury, with subsequent resolution by 2 weeks after injury. Collagen type II protein fragments were elevated in the synovial fluid and serum after injury. hBM-MSCs-Luc were detected immediately after injection and at 2 weeks after injection using fluorescence imaging, MRI, and bioluminescence imaging. Conclusion: This study demonstrates the feasibility of reproducing the chondral changes, intra-articular cytokine alterations, and body fluid biomarker findings consistent with PTOA after ACL injury in a large animal model. Furthermore, we have demonstrated the ability of hBM-MSCs to survive and express transgene within the knee joint of porcine hosts without immunosuppression for at least 2 weeks. Clinical Relevance: This model holds great potential to significantly contribute to investigations focused on the development of cell-based therapies for human ACL injury–associated PTOA in the future (seeAppendix Figure A1, available online).